The Construction of the Main Child Character's Identities in the Film Matilda (1996) - Chitra Yunia Mahmudah, - (2018)
This study entitled The Construction of the Main Child Character's Identities in the Film Matilda (1996) aims to reveal the construction of Matilda's identities and to derive meanings behind the construction. This study uses textual analysis and employs theories of identities from Burke and Stets (2009) as well as Boggs and Petrie's (2008) concept of characterizations, and film style from Bordwell and Thompson (2008). The findings show that Matilda has multiple identities which are constructed based on three person and role identities, and one group identity. Her multiple identities are established through her characterization and supported by cinematic aspects such as shot, color, lighting, and sounds. The analysis confirms Raburu's (2015) argument that identity has been constructed and developed in childhood. Thus, her character is seen as a non-mainstream construction. It is presented to be more mature than and not necessarily as innocent as most child characters in general.